Urban Response For Architectural Transformations In The Traditional City - AlJumaily, Saad; AbdulMajeed, Rafal A. (Sulaimani Journal for Engineering Sciences, 2019)
Cities as a design didn’t appear in existent directly but it comes from growth, changing and permanent response to human requirements over decades. Also, each generation takes what others produce, rearrange and replace. Thus, the city is a developing structure that responds to human needs through which a system that includes relationships and essential joints. Each city in the world depends on urban structure and Infra-structure. This research studies the transformations which happened to the traditional cities that come from technology, political, and economic challenges. These challenges try to inventory the city from its architectural characteristics, on the other hand, some of these challenges became the motivation to develop cites and response with technological development. Therefore, the problem of the research is the architectural transformations which are the result of high development for the traditional cities missed the urban and environmental forms that were present in the traditional cities. This research aims to identify the reconciliation the changeable architectural formations and attempting at benefit from urban influences of the traditional cities. The research finding that the process of continuation and dealing with the modern idea is an essential issue, because the holding on the ancient without awareness that leads to lose all structural characteristics of the city, and becomes just a skeleton without any functional and aesthetic spirit.
Keywords: Architectural Transformations; Traditional City; human needs